PENGEMBANGAN BAHAN AJAR FISIKA SMA TENTANG PENGUKURAN RESISTANSI BATUBARA, KAOLIN, DAN ANDESIT DENGAN METODE RESISTIVITAS MENGGUNAKAN KONSEP LISTRIK DINAMIS - Made Sari Rahayu; Partono . (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The research wasdone insenior high school(SMA/MA). Observations and interviewsin senoir high (SMA)in Seputih Raman, showedthat physic’s teachers haven’t developed student’s knowledge about lessons are teached include give examples daily aplication of lesson are teached by them. Include physic’s lesson about dinamis’selectricity. So, base onthe descriptionneed todo research on thedevelopment of physic’s materialteachingfor senior high school about measuring coal, kaolin, and andesit resistance by resistivity method usedinamis’s electricity concept . The research is development research by design physic’s materialteachingfor senior high school about measuring coal, kaolin, and andesit resistance by resistivity method usedinamis’s electricity concept, then tested its feasibilityby physic’s experts and base on student’s respons and reparation. Base on the result of research, expert test to feasibility and easy to understand the material at 79,2%, and student’s respons in the school to teaching material at 81,9%. Base on teh result, so can be concluted that there is teaching materialfeasibility that had been developed and appropriate to use in learning. Advice from researcher, it is hoped thatthefurther development soarrangeddinamis’s electricityteaching material is better in material’s explianing and the development.